Champion : A Legend Novel - Lu, Marie 1984- (New York, NY : G.P. Putnam's Sons, an imprint of Penguin Group (USA), 2013)
"June and Day have sacrificed so much for the people of the Republic--and each other--and now their country is on the brink of a new existence. Just when a peace treaty is imminent, a plague outbreak causes panic in the Colonies, and war threatens the Republic's border cities"--
Keywords: Plague -- Juvenile fiction; Plague -- Fiction; Love -- Fiction; Science fiction